Quality of life associated factors in head and neck cancer patients in a developing country using the FACT-H&N - Bilal, S.; Doss, J.G.; Cella, D.; Rogers, S.N. (2015)
Health-related quality of life (HRQoL) associated factors are vital considerations prior to treatment decision-making for head and neck cancer patients. The study aimed to identify potential socio-demographic and clinical prognostic value of HRQoL in head and neck cancer patients in a developing country. The Functional Assessment of Cancer Therapy-Head and Neck (FACT-H&N)-V4 in Urdu language was administered among 361 head and neck cancer patients. Data were statistically tested through multivariate analysis of variance (MANOVA) and regression modeling to identify the potentially associated factors. Treatment status, tumor stage and tumor site had the strongest negative impact on patients HRQoL, with a statistically significant decrement in FACT summary scales (effect size >0.15). Moderate associated factors of HRQoL included treatment type, marital status, employment status and age (effect size range 0.06-0.15). Weak associated factors of HRQoL with a small effect size (>0.01-0.06) included tumor size and type, gender, education level and ethnicity. This study reports 12 socio-demographic and clinical variables that have a significant impact on HRQoL of head, and neck cancer patients, and that should be considered during treatment decision-making by multidisciplinary teams and also in future HRQoL studies conducted in other developing countries. (C) 2014 European Association for Cranio-Maxillo-Facial Surgery. Published by Elsevier Ltd.